Hubungan Kematangan Beragama Dengan Perilaku Altruistik Mahasiswa Fakultas Dakwah Dan Komunikasi UINSU - Irma Oktavia; Husnia Amro; Fadilla Hafizah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research is entitled "The Relationship between Religious Maturity and Altruistic Behavior of Students at the Faculty of Da'wah and Communication, UINSU," which aims to determine religious maturity and altruistic behavior of students at the Faculty of Da'wah and Communication, UINSU. Basically, every human being has good characteristics, but it is seen from how the environment around them shapes their characteristics. One of the important things that must be considered in religion is maturity in religion. Because mature religiousness for each individual will lead that individual to a belief that apart from having a good relationship with God, he will also have a good relationship with other people around him. Seeing the condition of religious maturity with an altruistic attitude among FDK UINSU students, the behavior of helping each other and the spirit of family have almost disappeared in social life. Most students almost don't care about what happens in their surrounding environment. A person who has religious maturity is someone who is able to understand and apply the religious values ​​he adheres to in everyday life. The aim of this research is to determine the level and relationship between religious maturity and the behavior of FDK UINSU students in 2023. This type of research uses quantitative methods. The research was carried out at the Faculty of Da'wah and Communication, with a total of 70 samples, the sample used was data collection using a Likert scale model questionnaire with yes or no answers, namely the religious maturity scale and the altruistic behavior scale. Supporting data in this research is through observation and questionnaires.